Design and Fabrication of 6 Meter Fiberglass Boat for Coastal Water Tourism in Batam - Saputra, Hendra; Cahyagi, Danang; Perkasa, Veryawan Nanda; Purnama, Dedi; Nurmannsyah, Oxa; Saputra, Rangga; Ferari, Regita; Al Fauzy, Faaza Ibnu; Fadillah, Muhammad (International Journal of Marine Engineering Innovation and Research, 2024)
As an area with geographical conditions consisting of many islands, marine tourism in Batam has become a special attraction which has been developed through hotel investment, and coastal water tourism and travel-related services. Even though the demand is quite high, the availability of tourism boats to support coastal water tourism has low participation of the domestic industry. Therefore, this study aims to develop a tourism boat prototype designed and fabricated for coastal water tourism and travel-related services in Batam. This study began by studying the characteristics of coastal water, characteristics of tourism needs, design and development, and fabrication activities. Fiberglass is the material in shipbuilding because of the ease of the manufacturing process, and produces less waste and emissions. Based on the study results, it was found that the tourism boat needed is a 5 person capacity tourism boat with a length of 6 meters which can require 1 x 45 HP of power to reach a speed of 25 knots.As an area with geographical conditions consisting of many islands, marine tourism in Batam has become a special attraction which has been developed through hotel investment, and coastal water tourism and travel-related services. Even though the demand is quite high, the availability of tourism boats to support coastal water tourism has low participation of the domestic industry. Therefore, this study aims to develop a tourism boat prototype designed and fabricated for coastal water tourism and travel-related services in Batam. This study began by studying the characteristics of coastal water, characteristics of tourism needs, design and development, and fabrication activities. Fiberglass is the material in shipbuilding because of the ease of the manufacturing process, and produces less waste and emissions. Based on the study results, it was found that the tourism boat needed is a 5 person capacity tourism boat with a length of 6 meters which can require 1 x 45 HP of power to reach a speed of 25 knots.